1990
DOI: 10.1177/039139889001300807
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis-Associated Febrile Episodes: Surveillance before and after Major Alteration in the Water Treatment System

Abstract: Surveillance for bacteremic or pyrogenic episodes associated with hemodialysis was undertaken before and after the reconstruction of the water treatment system at our University medical center. The new water system included a holding tank with iodination treatment. The water delivered to individual dialysis stations had only occasional positive bacterial cultures (3 of 21 samples before completion of construction, 2 of 16 samples afterwards) and intermittent detection of endotoxin (6 of 21 samples before compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Sepsis-related fever is generally due to release of pyrogens and toxins by the pathogens which in turn trigger secretion of interleukins (IL) especially IL 1 and 6 and chemokines which cause thermogenesis and hypercatabolism. Some studies have documented this as well [26], [27]. Significant blood loss, chest pain and pruritus were the other minor complications documented and these have been documented in former similar studies [28], [29].…”
Section: Discussionmentioning
confidence: 61%
“…Sepsis-related fever is generally due to release of pyrogens and toxins by the pathogens which in turn trigger secretion of interleukins (IL) especially IL 1 and 6 and chemokines which cause thermogenesis and hypercatabolism. Some studies have documented this as well [26], [27]. Significant blood loss, chest pain and pruritus were the other minor complications documented and these have been documented in former similar studies [28], [29].…”
Section: Discussionmentioning
confidence: 61%
“…However, this was only apparent with high‐flux dialysis and the use of filtered dialysate, which corresponded to 10 fewer pyrogenic reactions in more than 28,000 treatments (19). Other authors have not found an association between pyrogenic reactions and the bacterial count or endotoxin level in the dialysate (20,21). Finally, LAL reactive material present in the blood, derived from cellulose‐based membranes, does not induce febrile reactions (22).…”
Section: Potential Clinical Consequencesmentioning
confidence: 94%